Recreational cannabis reduces rapes and thefts: Evidence from a quasi-experiment - Davide Dragone; Giovanni Prarolo; Paolo Vanin; Giulio Zanella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
An argument against the legalization of the cannabis market is that such a policy would increase crime. Exploiting the recent staggered legalization enacted by the states of Washington (end of 2012) and Oregon (end of 2014) we show, combining difference-in-differences and spatial regression discontinuity designs, that recreational cannabis caused a significant reduction of rapes and thefts on the Washington side of the border in 2013-2014 relative to the Oregon side and relative to the pre-legalization years 2010-2012.
Keywords: K23; K42; 330